The coyote - Mattern, Joanne, 1963- (Mankato, Minn. : Capstone High/Low Books, 1999)
Details the characteristics, habitats, and life cycle of the coyote.
Includes bibliographical references (p. 45) and index.
3.6
5-8
Keywords: Coyotes -- Juvenile literature; Coyotes; Coyotes